IKONOGRAFI TOPENG MALANG DALAM TOKOH DEWI SEKARTAJI DAN PANJI ASMOROBANGUN - Fatmawati, F.,; Zurinani, Siti (Acintya, 2016)
The shape and character masks in each region are rooted from local values and mythology in the local community. Each element of line, color, and pattern on the mask is a symbol that implies meaning. Panofski describe art object studies includes three stages. The first stage is called pre iconography, such as the interpretation of the textual aspect of a work of art is accompanied expressionalresponse. The second stage is called the stage of iconography, such as the interpretation of the theme and concept embodied in a work of art and the correction of the themes and concepts, and the third stage is called the stage of iconology, in the form of interpretation of the meaning in the context ofsocio-cultural. The third stage of the process are found to form, meaning and benefits of the existence of Malang Mask for society.Keywords: iconography, malang’s mask, Dewi Sekartaji, Panji Asmorobangun